CHARACTERISTICS, EFFICIENCY OF LIGHT-STRENGTH CONCRETE - Yusupova Lola; Yangiboyev Shahrizod (Journals Park Publishing, 2022)
In this article, the construction of tall, multi-story, complex buildings and structures based on ordinary heavy concrete, the construction use of lightweight concrete, as well as the efficiency of light and strong concrete in the field of construction. Detailed information is provide on structural solutions to reduce the labor force as much as possible in the preparation of structures, and at the same time to use lightweight strong concrete instead of heavy concrete.
Keywords: Construction, construction materials, heavy concrete, lightweight concrete, technological solution